Thematic Content Analysis: Is There a Difference Between the Support Provided by the MAXQDA® and NVivo® Software Packages? - Oliveira, Mirian; Bitencourt, Claudia Cristina; Santos, Ana Clarissa Matte Zanardo dos; Teixeira, Eduardo Kunzel (Revista de Administração da UFSM, 2015)
Content analysis is widely used in qualitative research. It can be organized into three approaches: lexical analysis (nature and richness of the vocabulary), syntactic (verb tenses and modes) and thematic (themes and frequency), used complementarily or separately, depending on the research objective. Whatever the approach, the volume of data is usually large and qualitative data analysis software could help simplify the operational activities. The aim of this study is to analyze the contribution of the NVivo® and MAXQDA® software packages in thematic content analysis. Achieving this objective involves a review of the main characteristics of thematic content analysis and an examination of both software packages, and finally, a comparison between them. The main results are: the similarity between the features available for qualitative data analysis in the two software packages and the differences in their interfaces. The potential gain provided by using these packages depends on the researcher’s knowledge of content analysis since they do not substitute the researcher in the coding process. A considerable reduction in execution time of the analysis, as well as the possibility of applying different filters are important benefits obtained aiding the researcher to reflect on the data collected and obtain inferences.